Financial and Non-Financial Disclosure Practices in Selected Awqaf Institutions - Muhammad Iqmal Hisham Kamaruddin; Rosnia Masruki; Mustafa Mohd Hanefah (International Journal of Nusantara Islam, 2018)
It is undeniable fact that waqf becomes as one of tools used in order to alleviate inequality among people especially Muslim community. Basically, waqf fund is raised from the public and managed by mutawalli under waqf institution. As the intermediate party between waqif and beneficiaries, waqf institution is accountable for the management of waqf funds and need to disclose sufficient information pertaining to waqf fund itself. Good disclosure practices by waqf institution should cover both financial and non-financial information for all related waqf activities, programs and projects conducted. This includes such as corporate information, strategic information, financial performance information, financial statement information and non-financial performance information. To examine such disclosure practices, intensive content analysis was employed on waqf reporting information which is waqf annual report from three selected awqaf institutions namely, Perbadanan Wakaf Selangor (PWS), Pusat Wakaf MAIWP Sdn Bhd (PWM) and Majlis Ugama Islam Singapura (MUIS). The results revealed that financial statement information was the highest disclosure practice by selected awqaf institutions when it scores 100% (385 out of 385 items), followed closely by strategic information 68.9% (62 out of 90 items), financial performance information 66.7% (80 out of 120 items), corporate information 61.7% (74 out of 120 items) and finally by non-financial performance information 37.5% (45 out of 120 items). Besides, several interesting and advanced disclosure practice by MUIS also highlighted and discussed as a benchmark for other awqaf institutions to disclose their waqf activities, programs and projects in the future.